Quantitative assessment of the reproducibility of functional activation measured with BOLD and MR perfusion imaging: implications for clinical trial design. - Tjandra, T; Brooks, J; Figueiredo, P; Wise, R; Matthews, P; Tracey, I (2005)
BOLD contrast is the most commonly used functional MRI method for studies of brain activity. However, the underlying physiological processes giving rise to measured BOLD signal changes (which include contribution from changes in cerebral blood flow (CBF), cerebral blood volume (CBV) and cerebral metabolic rate of oxygen consumption (CMRO2)) vary substantially between sessions and subjects. To determine whether direct CBF measurement is a more reliable technique, we compared the localisation of activation and reproducibility of relative signal change measured by optimised BOLD versus CBF measured using the arterial spin labelling (ASL) technique. Data were collected within the primary sensorimotor cortex in normal healthy controls performing a simple finger-tapping task over three imaging sessions (two on same day and one on a different day). The displacement between the foci of BOLD and CBF activation was less than the linear dimension of one voxel (2.4 mm), however, BOLD activation was significantly closer to the nearest draining vein compared to CBF activation (P=0.030). For the relative signal change measurement, we found that CBF has a lower inter-subject variation than BOLD (P<0.05), enabling a smaller sample size for any given effect size, although the intra-subject variation across sessions for CBF was not significantly different from BOLD. BOLD imaging provides the optimal contrast for exploratory brain activation mapping, however, for a single time-point group study, CBF has reduced variance. In addition, the reduction of variance over time using CBF measurements (non-significant) suggests it could potentially provide a more useful approach when assessing longitudinal activation changes.